The Node Energy of Multipath Routing Protocol for Mobile Ad Hoc Networks - Sangeetha, S.J; Rajendran, T (International Journal of Computer Sciences and Engineering, 2025)
In this research, a cross-layer optimized energy-aware multipath routing protocol (EMRP) for mobile ad hoc networks (MANET) is proposed. By sharing the information among the physical layer, the MAC sub-layer and the network layer, EMRP efficiently utilizes the network resources such as the node energy and the link bandwidth. Simulation results show that the protocol prolongs the network lifetime, increases the volume of packets delivered, lowers the energy dissipation per bit of data delivery and shortens the end-to-end delay. The growth of interest and research on multihop wireless network is exponential in recent years. In mobile ad hoc networks (MANET), the nodes play the role of routers to forward the packets of neighbor nodes as there is no fixed infrastructure available to do so. Network is a proven solution that maps the architecture of cellular networks into ad hoc networks. Here, selected nodes form the virtual backbone of the network and take part in packet routing. This achieves faster packet delivery as limited nodes are responsible for the same even though the network is not strongly connected. In this paper, a distributed topology adaptive clustering algorithm is designed that requires local information by the nodes for the formation of clusters. The role of cluster head is fairly distributed among the nodes to obtain a longer network lifetime. The change of cluster heads and the mobility of nodes disturb the node connectivity resulting in communication instability. To overcome such situations, a topology control protocol is developed that adjusts the transmission range of concerned mobile nodes to achieve local connectivity among nodes within the clusters even after the hand-off by the heads takes place